Prevalence and Correlates of Self-Reported ADD/ADHD in a Large National Sample of Canadian Adults. Issue 2 (January 2018) - Hesson, Jacqueline; Fowler, Ken
Objective: The objective of this study was to examine the prevalence and correlates of self-reported attention deficit disorder (ADD)/ADHD in Canadian adults.Method: Prevalence of self-reported ADD/ADHD was examined in a large national sample of Canadians ( n = 16, 957). Demographic variables, lifetime, and current psychiatric comorbidities were then compared in a group of adults with self-reported ADD/ADHD ( n = 488) and an age- and gender-matched control group ( n = 488).Results: The prevalence of self-reported ADD/ADHD was 2.9%. Significantly higher lifetime and current prevalence rates of major depressive disorder, bipolar I and II disorders, generalized anxiety disorder, and substance use disorders were observed in the ADD/ADHD group compared with the control group. Within the ADD/ADHD group, lifetime and 12-month prevalence rates of major depressive disorder and generalized anxiety disorder were significantly higher in women, whereas lifetime and current rates of some substance use disorders were significantly higher in men.Conclusion: In a national sample of Canadian adults, self-reported ADD/ADHD was associated with significant psychiatric comorbidity. Gender differences were also noted.